Sosialisasi Edukasi Imunisasi Dan Tumbuh Kembang Anak Untuk Meningkatkan Pengetahui Ibu Di Posyandu Puskesmas PB Selayang II Medan - Maria Haryanti Butar-Butar; Byba Melda Suhita; Siska Saidi Rizali; Sri Yuni Windu Puri; Nurwijayanti Nurwijayanti (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Stimulation of child growth and development is carried out by mothers, fathers, caregivers and other family members who are the closest people to the child. The purpose of this socialization activity is to determine the knowledge of mothers who have children about immunization and child growth and development. The activity was carried out at Puskesmas PB. Selayang II Medan with the team at the posyandu with preparations that have been made with the steps achieved. This activity is a socialization of Health Education to mothers by distributing leaflets and lectures as well as pre and post activities. The results of the pre-activity were found from 34 participants who had the highest score of 100 as many as 9 people and the lowest score of 10 as many as 1 person, and after the socialization was carried out, the results for the post of 34 mothers who had the lowest score of 80 as many as 6 people and the rest scored 100. So that the results of the difference before with a percentage of 71.7% and after 96.5% with the average value is 24.8. The conclusion of the activity that this activity is very useful for mothers to increase mothers knowledge about immunization and child growth and development so that this socialization is very useful for changing mothers to be able to understand about immunization and child growth and development so that early prevention of stunting can be done.